Effect of Carica Papaya L Leaf Infusion on Transporting Glucose across Small Intestine Cell Membrane of Wistar Rats Model - Srisathis Renganathan; Vycke Yunivita; Anna Martiana S; Nida Suraya (Althea Medical Journal, 2019)
Background: Carica papaya L leaf is one of the common types of plant that has been used as treatment for diabetes mellitus (DM). The leaf possibly contain quercetin, which may inhibit glucose transport through cell membrane of small intestine. This study was conducted to determine the effect of Carica papaya L leaf infusion on glucose transport in Wistar rat model.Methods: A one-group pretest-posttest explorative study was designed using perfusion method. Nine male rats were fasted for 18-24 hours before dissected. A 25 mL glucose solution was given as early control, before Carica papaya L leaf infusion treatment A 25 mL glucose solution was later given again after Carica papaya L leaf infusion as late control. Artificial perfusion equipment had been used to maintain the back and forth flow of glucose in the small intestine. Sample was taken every 15 minutes for one hour for each treatment.Results: Carica papaya L leaf infusion did not decrease the concentration of glucose absorption significantly compared to early control. The mean absorption of glucose in early control was 85.39+4.42 mg/dl and during treatment was 84.51+4.20 mg/dL.Conclusions: Carica papaya L leaf infusion does not have significant inhibiting effect on glucose transport across small intestine cell membrane. Further explorative study is required.